Pancreatic Tuberculosis mimicking Cystic Neoplasm - Jha, Anamika (Journal of Society of Surgeons of Nepal, 2017)
Tuberculosis is endemic in our part of the world and may have uncommon presentations like pancreatic involvement. A young male presented to the OPD with recent history of pain in epigastric region and was subsequently diagnosed with a multi-loculated cystic neoplasm in pancreatic head region on ultrasonography and CT scan. The pancreatic origin was confirmed on surgery while the histopathological study revealed tuberculous nature. This case report highlights the importance of considering tuberculosis in the differential diagnosis in pancreatic masses, especially, with atypical appearances, in young patients or with background predisposing to TB and the need for histological diagnosis.